THE ROLE OF CHEMOKINES IN FIBROMYALGIA - Tuba Tülay Koca; Muhammed Seyithanoğlu; Fırat Sakınmaz (Rheumatology Quarterly)
Aim: Chemokines are cytokines that cause chemotaxis to leukocytes and stem cells in inflammation and homeostasis. Fibromyalgia (FM) is characterized by widespread chronic pain and somatic symptoms. The role of immun mediators in the pathogenesis of FM is the topic of recent researches and current evidence supports that chemokines are important in the syndrome’s pathogenesis. In our study, the importance of some chemokines and their receptors in FM and their relationship with pain and disease severity are analyzed. Material and Methods: This is a cross-sectional analytic study. Our study included 40 female patients with FM (American College of Rheumatology, 2016) and 40 healthy controls matched for age and body mass index (BMI). C-C motif chemokine receptor 3, chemokine (C-C motif) 4 (CCL4), and macrophage-derived chemokine (MDC) levels were measured in the blood samples of the participants using the enzyme-linked immunosorbent assay. Pain and disease severity in FM patients were evaluated with a visual analog scale (VAS, 0-10 cm) and Fibromyalgia Impact Questionnaire (FIQ), respectively. Results: The groups were similar in terms of age (p=0.19) and BMI values (p=0.109). C-reactive protein (p=0.013), MDC (p=0.016), and CCL4 (p=0.026) values were higher in the FM group. The mean VAS of the FM group was 7.5±2.5 cm, while the FIQ was 61.1±14.9. Conclusion: MDC and CCL4 chemokines can be used as helpful parameters in diagnosing FM with moderate sensitivity and specificity. High levels of chemokines in the FM group support the role of chemokines in the etiopathogenesis of disease through immunomodulation in the nervous system.